Use of XAS for the elucidation of metal structure and function: applications to nickel biochemistry, molecular toxicology, and carcinogenesis. - Carrington, Paul E (2002)
Nickel has been shown to be an essential trace element involved in the metabolism of several species of bacteria, archea, and plants. In these organisms, nickel is involved in enzymes that catalyze both non-redox (e.g., urease, glyoxalase I) and redox (e.g., hydrogenase, carbon monoxide dehydrogenase, superoxide dismutase) reactions, and proteins involved in the transport, storage, metallocenter assembly, and regulation of nickel concentration have evolved. Studies of structure/function relationships in nickel biochemistry reveal that cysteine ligands are used to stabilize the Ni(III/II) redox couple. Certain nickel compounds have also been shown to be potent human carcinogens. A likely target for carcinogenic nickel is nuclear histone proteins. Here we present X-ray absorption spectroscopic studies of a model Ni peptide designed to help characterize the structure of the nickel complexes formed with histones and place them in the context of nickel structure/function relationships, to gain insights into the molecular mechanism of nickel carcinogenesis.